2011
DOI: 10.3109/10428194.2011.584005
|View full text |Cite
|
Sign up to set email alerts
|

Development of imatinib and dasatinib resistance: dynamics of expression of drug transportersABCB1, ABCC1, ABCG2, MVP, and SLC22A1

Abstract: About 20% of patients with chronic myeloid leukemia (CML) do not respond to treatment with imatinib either initially or because of acquired resistance. To study the development of CML drug resistance, an in vitro experimental system comprising cell lines with different resistance levels was established by exposing K562 cells to increasing concentrations of imatinib and dasatinib anticancer agents. The mRNA levels of BCR- ABL1 and of genes involved in drug transport or redistribution (ABCB1, ABCC1, ABCC3, ABCG2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 38 publications
3
58
1
Order By: Relevance
“…It is well known that ABCG2 has important roles in MDR in leukemia (20,21). Therefore, to evaluate the effects of NEAT1 on the MDR of leukemic cells, the expression level of ABCG2 was detected by western blotting.…”
Section: Neat1 Overexpression Inhibits Abcg2 Transporter Protein Exprmentioning
confidence: 99%
“…It is well known that ABCG2 has important roles in MDR in leukemia (20,21). Therefore, to evaluate the effects of NEAT1 on the MDR of leukemic cells, the expression level of ABCG2 was detected by western blotting.…”
Section: Neat1 Overexpression Inhibits Abcg2 Transporter Protein Exprmentioning
confidence: 99%
“…However, Giannoudis et al [42] postulated that the uptake is likely passive diffusion because of the lipophilic properties of dasatinib. On the other hand, they state that the role of other uptake transporters could not be excluded [43]. In our hands there is a clear difference between 4 °C and 37 °C, indicating an active transport.…”
Section: Discussionmentioning
confidence: 62%
“…De Vries et al [45] also suggested the involvement of P-gp in the efflux of erlotinib. Giannoudis et al [42] and Gromicho et al [43] suggested that P-gp is also involved in dasatinib dependent efflux. The effect of hOCT inhibitors on sunitinib and crizotinib was similar, except for verapamil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, imatinib and dasatinib are the most preferred synthetic drugs among many, against chronic myeloid leukemia (CML) and colorectal cancer. However, in the accelerated phase of CML and the advanced stage of colorectal cancer, the emerged drug-resistant cancer cells predominate, with eventual metastatic invasion of cancer to internal tissue, resulting in the transfer of patients to hospice (Hochhaus et al 2007;Gromicho et al 2011). Moreover, drug-resistant cancer cells need be addressed suitably to overcome the impasse in treatment; most established anticancer drugs cannot be replaced ordinarily, due to sporadic developments of resistant cancer stem cells.…”
Section: Introductionmentioning
confidence: 97%